"What works?" Systematic reviews and meta‐analyses of the investigative interviewing research literature. Issue 2 (19th February 2021) - Meissner, Christian A.
Abstract: While the practice of investigative interviewing has traditionally been grounded in customary knowledge, decades of research have now enhanced our understanding of the limits of these practices and led to the development of novel, theoretically informed approaches. The maturity of any science is likely best evidenced in the conduct of systematic reviews and meta‐analyses, and the investigative interviewing research literature has reached just such a period in its development. This paper reviews current "best practices" in research synthesis, describes the variety of meta‐analyses conducted in the investigative interviewing research literature to date, and introduces the nine reviews that comprise the current special issue. It concludes by summarizing the lessons learned from these syntheses with respect to improving our research methods, measures, and approaches in the investigative interviewing literature.